2022
DOI: 10.3390/nano12193418
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Coupling and Modulation of van der Waals Heterostructures for Nanodevices

Abstract: In recent years, van der Waals heterostructures (vdWHs) of two-dimensional (2D) materials have attracted extensive research interest. By stacking various 2D materials together to form vdWHs, it is interesting to see that new and fascinating properties are formed beyond single 2D materials; thus, 2D heterostructures-based nanodevices, especially for potential optoelectronic applications, were successfully constructed in the past few decades. With the dramatically increased demand for well-controlled heterostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 153 publications
0
7
0
Order By: Relevance
“…Several early experiments investigated the impact of temperature on the phononic properties of few-layered TMDs, including MoS 2 , WS 2 , MoSe 2 , and others [ 21 ]. These studies have demonstrated that temperature-dependent behaviors of phononic modes in these nanosheets are attributed to the effects of thermal expansion and anharmonic resonance [ 22 ]. Moreover, some studies investigated the impact of interlayer coupling on the Raman spectra of TMDs heterostructures, which demonstrated a strong dependence on the stacking orientation of the constituent monolayers [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several early experiments investigated the impact of temperature on the phononic properties of few-layered TMDs, including MoS 2 , WS 2 , MoSe 2 , and others [ 21 ]. These studies have demonstrated that temperature-dependent behaviors of phononic modes in these nanosheets are attributed to the effects of thermal expansion and anharmonic resonance [ 22 ]. Moreover, some studies investigated the impact of interlayer coupling on the Raman spectra of TMDs heterostructures, which demonstrated a strong dependence on the stacking orientation of the constituent monolayers [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interlayer coupling plays a fundamental role not only in the electronic properties of vdW heterostructures but also in the vdW gap. , Recently, Z. Wu et al demonstrated that nonvolatile memristive forming can eliminate the vdW gap between 2D channels and contact electrodes, thus reducing the contact resistance by at least 1 order of magnitude . Besides the type-I Dirac semimetal represented by graphene, the layered PtTe 2 as a type-II Dirac semimetal is an emerging semimetallic material and has wide-ranging potential applications in mid-infrared and even terahertz photodetection. , It has been experimentally verified that PtTe 2 as electrodes can reduce contact resistance through an edge-to-edge connection between PtTe 2 and 2D semiconductors. , Those edge contacts based on a lateral heterostructure synthesized by the CVD route are incompatible with current semiconductor manufacturing processes .…”
Section: Introductionmentioning
confidence: 99%
“…21,27 Interlayer coupling plays a fundamental role not only in the electronic properties of vdW heterostructures but also in the vdW gap. 28,29 Recently, Z. Wu et al demonstrated that nonvolatile memristive forming can eliminate the vdW gap between 2D channels and contact electrodes, thus reducing the contact resistance by at least 1 order of magnitude. 30 Besides the type-I Dirac semimetal represented by graphene, the layered PtTe 2 as a type-II Dirac semimetal is an emerging semimetallic material and has wide-ranging potential applications in midinfrared and even terahertz photodetection.…”
Section: Introductionmentioning
confidence: 99%
“…The study of geometric nonlinear aeroelasticity differs from general aeroelasticity [1] from the theoretical aspects as follows: One is the structural geometric nonlinear theory, which mainly addresses the static and dynamic analysis of the structure under large deformation [2][3][4]; The other is the study of surface aerodynamic theory [5], which mainly addresses the boundary condition dependent deformation state aerodynamic calculation method under large deformation conditions of the structure [6]; The third is the study of the structural/aerodynamic interface coupling method [7,8], which mainly investigates the multidimensional interpolation problem applicable to large deformation in space. The problem of subsonic aeroelasticity of plates focuses on the fluid-structure coupling between the structure and the airflow [9,10].…”
Section: Introductionmentioning
confidence: 99%